Carcass evaluation procedures compared - Kropf, Donald H.; Bergkamp, J.L.; Berroth, J.N. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
This study compared various methods of evaluating carcasses. Data from 57 barrows on feeding trials for a barrow contest at the 1968 Kansas State Fair in Hutchinson were used.The barrows went on test weighing approximately 50 pounds each and were taken off feed individually at 200- 220 pounds, held off feed over night and slaughtered at the Kansas State University Meats Laboratory. Live weight was determined immediately before slaughter and carcass weight, after a 24-hour chill. Cutting time ranged from 24 to 120 hours post-mortem.
Swine Industry Day 1969 is known as Swine Day, 1969
Keywords: Swine; Barrows; Carcass